Formation of Saccular Cerebral Aneurysms May Require Proliferation of the Arterial Wall: Computational Investigation - Yuji SHIMOGONYA; Takuji ISHIKAWA; Yohsuke IMAI; Daisuke MORI; Noriaki MATSUKI; Takami YAMAGUCHI (Journal of Biomechanical Science and Engineering, 2008)
We have performed numerical simulations to examine saccular cerebral aneurysm formation at the outer curve of a bent artery. A U-shaped arterial geometry with torsion, which was modeled on part of the human internal carotid artery, has been employed. A new numerical model was proposed to take into account proliferation as well as degradation of the arterial wall. Proliferation of the arterial wall was modeled by surface area expansion in high wall shear stress region. Based on wall shear stress distribution on the artery, we have investigated aneurysm formation for the following three conditions: (a) strength degradation of the wall, (b) proliferation of the wall, and (c) both strength degradation and proliferation of the wall. A saccular aneurysm shape was not observed when considering only arterial wall degradation up to 90%. However, the saccular shape formed when proliferation of the arterial wall was also taken into consideration. The resultant shape was consistent with clinical observations. Our findings have suggested that a saccular aneurysm may not be formed by degradation of the arterial wall alone, but also require its proliferation.